2024
DOI: 10.1016/j.jvoice.2021.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Kulning: Acoustic and Perceptual Characteristics of a Calling Style Used Within the Scandinavian Herding Tradition

Abstract: Kulning, a loud, high-pitched vocal calling technique pertaining to the Scandinavian herding system, has attracted several researchers' attention, mainly focusing on cultural, phonatory and musical aspects. Less attention has been paid to the spectral and physiological properties that characterize Kulning tones, and also if there is a physiologically optimum pitch range. We analyzed tones produced by ten participants with varying experience in Kulning. They performed a phrase, pitch range G5 to C6 (784 to 1046… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…16 The spectra of Opera and Kulning were both characterized by strong H1. This feature has been reported for soprano singing in several earlier studies 16,21,22 and for Kulning by Johnson et al 6 and Rosenberg et al 23 In the present study, the most substantial spectral differences between Opera and Kulning were observed in H3, H4, and H5. In Operatic singing, the energy distribution above H1 seemed to concentrate near H3 and H4, while in Kulning, it was slightly higher near H5.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…16 The spectra of Opera and Kulning were both characterized by strong H1. This feature has been reported for soprano singing in several earlier studies 16,21,22 and for Kulning by Johnson et al 6 and Rosenberg et al 23 In the present study, the most substantial spectral differences between Opera and Kulning were observed in H3, H4, and H5. In Operatic singing, the energy distribution above H1 seemed to concentrate near H3 and H4, while in Kulning, it was slightly higher near H5.…”
Section: Discussionsupporting
confidence: 89%
“…From this data, it is not possible to determine if the tuning of R2 or R3 occurs in Kulning. Rosenberg et al discussed the possibility of resonances being tuned to several of the lowest harmonics, 23 however, the findings of Johnson et al, who used acoustic models to estimate the frequencies of the four lowest resonances, supported only tuning of R1 to H1. 6 It should be considered that resonance tuning strategies are highly vowel dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…See also Aletta and Kang (2020) for examples of research on historical acoustics. 7 A rather drastic example of how stylistic development is constrained by the surrounding acoustics is kulning, herding calls found in Swedish traditional vocal music (Rosenberg et al, 2022). Acoustic characteristics that arose due to the desire to project sound over large distances remains as integral aspects of kulning, even when the practice is removed from its previous function and context, and instead performed on stage or in recording studios.…”
Section: Conceptual Considerationsmentioning
confidence: 99%